2005
DOI: 10.1111/j.1365-2036.2005.02311.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte telomere dynamics and telomerase activity in inflammatory bowel disease: effect of drugs and smoking

Abstract: SUMMARYBackground: The chromosome instability observed in peripheral blood lymphocytes in ulcerative colitis could be a biomarker of cancer susceptibility. Aim: To determine whether accelerated telomere shortening could explain chromosome instability and assess the effect of drugs and smoking on telomere dynamics in these cells. Methods: Peripheral blood lymphocytes were isolated from ulcerative colitis, Crohn's disease and noninflammatory bowel disease control patients. Telomere lengths were measured by quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
4
8
0
1
Order By: Relevance
“…The indication of an association between tobacco smoke exposure and TA provided by this work is in agreement with the results of a previous investigation, in which a smoke‐related increase of TA was observed in normal bronchial epithelium of smokers [Yim et al, ]. However, no smoke‐related differences in TA had been reported in previous studies in PBMCs from healthy individuals [Getliffe et al, ; Narducci et al, ; Jeon et al, ; Rentoukas et al, ]: this discrepancy may depend on the different study design, given that none of the cited studies, involving mixed study populations, was specifically designed to evaluate the relationship between smoking habits and TA, while the twin study design applied in the present work allowed a rigorous assessment of the influence of the study variable under identical genetic background.…”
Section: Discussionsupporting
confidence: 92%
“…The indication of an association between tobacco smoke exposure and TA provided by this work is in agreement with the results of a previous investigation, in which a smoke‐related increase of TA was observed in normal bronchial epithelium of smokers [Yim et al, ]. However, no smoke‐related differences in TA had been reported in previous studies in PBMCs from healthy individuals [Getliffe et al, ; Narducci et al, ; Jeon et al, ; Rentoukas et al, ]: this discrepancy may depend on the different study design, given that none of the cited studies, involving mixed study populations, was specifically designed to evaluate the relationship between smoking habits and TA, while the twin study design applied in the present work allowed a rigorous assessment of the influence of the study variable under identical genetic background.…”
Section: Discussionsupporting
confidence: 92%
“…This result indicates a partial contribution of age at blood donation to telomere length, consistent with previous observations (46,47). Valdes et al reported a significant reverse dose-dependent relationship of telomere length with smoking pack-years among 1,122 White women ages 18 to 76 years.…”
Section: Discussionsupporting
confidence: 81%
“…Smoking status, diet, socioeconomic status, stress level, and lifestyle might influence telomere dynamics. 62,98100 The sex hormones directly increase TERT transcription and telomerase activity in human cells. 24,101 Natural and synthetic androgens can restore telomerase activity to normal levels in cells in patients with TERT and TERC mutations 24 ; this probably explains the benefit of these agents in syndromes involving hematopoietic failure.…”
Section: Modulation Of Telomerase Activitymentioning
confidence: 99%